Pendampingan Demplot Teknik Budidaya Bawang Merah pada Musim Hujan Secara Ramah Lingkungan - Manan, Abdul; Soesanto, Loekas; Mugiastuti, Endang; Rahayuniati, Ruth Feti (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2024)
Background: Shallot cultivation in the rainy season faces the constraints of more severe plant disease problems. Utilization of mixed biopestisda Trichoderma harzianum, Bacillus sp. B8 and Pseudomonas flourescens P8 as well as proper cultivation techniques have not been adopted by farmers. It is necessary to assist farmers in implementing the technology The objectives of the activity are: assisting farmers in implementing the shallot cultivation technology package appropriately, increasing the quantity and quality of crop production, and increasing farmers' income through increasing farm efficiency. Method: The farmers participating in the activity are members of the farmer group